Strategi Guru Kelas 1 dalam Membangun Iklim Kelas yang Adaptif bagi Murid Baru pada Masa Transisi PAUD – SD - Siti Paridah; Muthmainah Muthmainah; Prayitno Prayitno (JEA (Jurnal Edukasi AUD), 2026)
The transition from early childhood education to elementary school is a crucial period that requires the support of an adaptive learning environment. Grade 1 teachers play a role in creating an adaptive classroom climate so that students can adapt to the demands of formal learning. This study aims to describe the strategies of grade 1 teachers in building an adaptive classroom climate for new elementary school students. This study uses a descriptive qualitative approach with a case study method. The research subjects consisted of 1 grade 1B teacher and 25 new students at Ulu Benteng 2 Public Elementary School. Data collection techniques were carried out through observation, interviews, and documentation. Data analysis used an interactive model that included data condensation, data presentation, and conclusions. The results of the study indicate that teachers implemented several strategies in creating an adaptive classroom climate, namely: (1) building positive emotional relationships with students; (2) implementing play-based learning; (3) creating a safe and enjoyable classroom environment. These strategies are used by teachers to support students in adjusting academically and socially at the beginning of elementary school. Therefore, the role of grade 1 teachers is very important in creating a learning environment that supports student adaptation.